Mesenchymal stromal cells in the treatment of pediatric hematopoietic cell transplantation-related complications (graft vs. host disease, hemorrhagic cystitis, graft failure and poor graft function): a single center experience - Pérez-Torres Lobato, Maria; Benitez-Carabante, Maria Isabel; Alonso, Laura; Torrents, Silvia; Castillo Flores, Nerea; Uria Oficialdegui, Maria Luz; Panesso, Melissa; Alonso-Martínez, Carla; Oliveras, Maria; Renedo-Miró, Berta; Vives, Joaquim; Diaz-de-Heredia, Cristina (Frontiers in Pediatrics, 2024)
Objectives: to describe mesenchymal stromal cells (MSCs) in the treatment of hematopoietic stem cell transplantation (HSCT) complications and to assess its safety and efficacy.Methods Single-center retrospective study (2016-2023). Patients under 20 years who received MSCs for the treatment of HSCT-related complications were included.Results: Thirty patients (53.7% boys), median age at transplant 11 years (range 2-19) were included. MSCs indications were: graft-versus-host disease (GVHD) in 18 patients (60%), of them 13 had acute GVHD (43.3%) and 5 chronic GVHD (16.6%); Grade 3-4 hemorrhagic cystitis (HC) in 4 (13.3%); poor graft function (PGF) in 6 (20%), 5 of them receiving MSCs with a CD34 stem cell-boost coinfusion; graft failure (GF) in 2 (6.7%), to enhance engraftment after a subsequent HSCT. Infusion-related-adverse-events were not reported. Overall response (OR) was 83%; 44% patients (11/25) showed complete response (CR). OR for GVHD, HC, PGF and GF was 83.3%, 100%, 66.7% and 100% respectively. Response rate was 40% (95%CI: 20-55) and 79% (95%CI:57-89) at 15 and 30 days. With a median follow-up of 21 months (IQR11-52.5), overall survival (OS) was 86% (95%CI:74-100) and 79% (95%CI:65-95) at 6 and 12 months post-MSCs infusion.In our study, the most frequent indication of MSCs was refractory aGVHD (43.3%). Response rates were high (OR 83%) and safety profile was good.